2009
DOI: 10.5433/1679-0359.2009v30n3p693
|View full text |Cite
|
Sign up to set email alerts
|

Tendinose do supra-espinhoso em cães

Abstract: ResumoA tendinose do supra-espinhoso é uma desordem recentemente relatada em cães e bem documentada em seres humanos, espécie na qual representa 51% das causas de alteração na articulação do ombro. Em cães, a afecção pode levar à dor na articulação acometida e claudicação ou permanecer assintomática. O significado clínico do problema ainda não foi definido na espécie canina e parece ser subestimado. O objetivo deste trabalho é discorrer sobre as possíveis etiologias desta tendinopatia e principais métodos diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Bone alterations, such as fractures and dislocations, are easily identified on radiographic evaluation. Alterations of the soft tissues involved in stabilizing the joint, such as tendonitis and muscle contractures, among others, are rarely identified in radiographic studies and require additional imaging techniques to obtain a diagnosis GERWING, 2001;MISTIERI, 2008;MISTIERI et al, 2012;SILVA et al, 2013).…”
Section: Anatomical Review and Clinical Relevancementioning
confidence: 99%
See 4 more Smart Citations
“…Bone alterations, such as fractures and dislocations, are easily identified on radiographic evaluation. Alterations of the soft tissues involved in stabilizing the joint, such as tendonitis and muscle contractures, among others, are rarely identified in radiographic studies and require additional imaging techniques to obtain a diagnosis GERWING, 2001;MISTIERI, 2008;MISTIERI et al, 2012;SILVA et al, 2013).…”
Section: Anatomical Review and Clinical Relevancementioning
confidence: 99%
“…For its assessment, the shoulder should be kept in an anatomical position, with an approximately 135 o flexion, and slightly rotated externally (LAFUENTE et al, 2009;MISTIERI, 2008). Although it does not cause discomfort, anesthesia is performed because the bicipital tendon is simultaneously evaluated in the same procedure, as retrospective studies have shown the relationship between the presence of large calcifications on the supraspinous tendon and bicipital tenosynovitis (MISTIERI, 2008;MURPHY et al, 2008).…”
Section: Supraspinatus Tendon and Musclementioning
confidence: 99%
See 3 more Smart Citations